Predicting streamflow in Peninsular Malaysia using support vector machine and deep learning algorithms - Essam Y.; Huang Y.F.; Ng J.L.; Birima A.H.; Ahmed A.N.; El-Shafie A. (Nature Research, 2023)
algorithm; Malaysia; river; support vector machine; Algorithms; Deep Learning; Malaysia; Rivers; Support Vector Machine